Calcineurin Regulates Progressive Motility Activation of Rhinella (Bufo) arenarum Sperm Through Dephosphorylation of PKC Substrates - Krapf, Dario (2014)
Animals with external fertilization, as amphibians, store their sperm in a quiescent state in the testis. When spermatozoa are released into natural fertilization media, the hypotonic shock triggers activation of sperm motility. Rhinella (Bufo) arenarum sperm are immotile in artificial seminal plasma (ASP, resembling testicular plasma tonicity) but acquire in situ flagellar beating upon dilution. However, if components from the egg shelly coat are added to this medium, motility shifts to a progressive pattern. Recently, we have shown that the signal transduction pathway required for in situ motility activation involves a rise in intracellular cAMP through a transmembrane adenylyl cyclase and activation of PKA, mostly in the midpiece and in the sperm head. In this report, we demonstrate that activation of calcineurin (aka PP2B and PPP3) is required for the shift from in situ to progressive sperm motility. The effect of calcineurin is manifested by dephosphorylation of PKC substrates, and can be promoted by intracellular calcium rise by Ca2+ ionophore. Both phosphorylated PKC substrates and calcineurin localized to the flagella, indicating a clear differentiation between compartmentalization of PKA and calcineurin pathways. Moreover, no crosstalk is observed between these signaling events, even though both pathways are required for progressive motility acquisition as discussed.